Potentiation of bleomycin cytotoxicity in Saccharomyces cerevisiae. - Moore, C W (1994)
Lesions introduced into cellular DNAs prelabeled with [2-14C]thymidine or [6-3H]thymidine, as well as cell killing, were inhibited by the presence of EDTA during 20-min reactions of Saccharomyces cerevisiae cells with the low-molecular-weight bleomycin family of anticancer antibiotics. In contrast, the level of killing by low concentrations of bleomycin was higher among cells which had grown for three generations in defined synthetic complete medium supplemented with ferrous sulfate than among cells grown without iron supplementation. In S. cerevisiae, the uptake of iron is facilitated by a plasma membrane ferric reductase activity and a high-affinity (Km = 5 x 10(-6) M) ferrous uptake system. Lethal effects of 1.3 x 10(-6) M bleomycin increased approximately 50% with 10(-5) M Fe(II), nearly twofold with 10(-4) M Fe(II), and 2.8 times with 10(-3) M Fe(II). Thus, iron preloading is a new experimental approach to increasing and studying the effects of the glycopeptides on cellular DNAs and other cellular targets. This approach could also be used for studying and better understanding DNA repair genes and could serve as a model for studies of redox active chemicals in biological systems.